Mechanical properties of magneto-sensitive shear thickening fluid absorber and application potential in a vehicle. (March 2022) - Liu, Bing; Du, Chengbin; Deng, Huaxia; Fan, Ziyang; Zhang, Junshuo; Zeng, Fanang; Fu, Yankai; Gong, Xinglong
Highlights: The magneto-sensitive shear thickening fluid (MSTF) with both shear thickening effect and magnetorheological performance was fabricated. The influence of the current, frequency and amplitude on the MSTF absorber was analyzed. The Cadillac magnetorheological shock absorber with commercial magnetorheological fluid (MRF) and self-made MSTF were tested. The variation rules of the compression force and rebound force were given. The self-made MRF and MSTF with distinct carbonyl iron powder (CIP) mass fractions were prepared and the influence of CIP on the damping force was studied. Abstract: A multifunctional smart material with both shear thickening effect and magnetorheological performance was fabricated by dispersing carbonyl iron powder (CIP) particles into shear thickening fluid, the properties and application potential were tested and analysed. Firstly, the rheological properties of this type of magneto-sensitive shear thickening fluid (MSTF) was tested by a rheometer. Besides, the influence of the current, frequency and amplitude on the mechanical properties of the absorber with MSTF was studied. Finally, the damping force and the variation rules of the Cadillac shock absorber with commercial magnetorheological fluid and MSTF were tested, compared and analysed at different currents and distinct velocities. The influence of the shear thickening effect of MSTF on the damping force in the shock absorber was studied by testing the self-made MSTF and MRF with the CIP fraction from 10% to 70%. This work provided a design idea to improve the shock absorber performance.